AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN WRITING HORTATORY EXPOSITION TEXT ABILITY (A Study at the Eleventh Grade Students of SMA Negeri 1 Pinangsori in 2018/2019 Academic Year) - Novita Mayasari Aritonang (JURNAL LINER (Language Intelligence and Educational Research), 2020)
The purpose of this research are to know: 1) The students’ ability in writing hortatory exposition text at the eleventh grade students of SMA Negeri 1 Pinangsori in 2018/2019 academic year, 2) The difficulties that faced by the students in writing hortatory exposition text at the eleventh grade students of SMA Negeri 1 Pinangsori in 2018/2019 academic year. This research is used mixed method; that is combination of qualitative and quantitative research. The informants of this research are 15 that representative from the eleventh grade students of SMA Negeri 1 Pinangsori. The data were collected by test and observation. Test was made to know the students’ ability in writing hortatory exposition text and the difficulties that faced by the students in writing hortatory exposition text ability at the eleventh grade students of SMA Negeri 1 Pinangsori, observation was made to know all of the activities or behaviours of the students in writing hortataory exposition text.The highest score 75, the lowest score 38, and the average score in writing hortatory exposition text 57.33 and it was categorized difficult, it means that students ability in writing hortatory exposition text are still difficult. The students had difficulty in using content 80%, using organization 73.33%, using vocabulary 73.33%, mastering grammar 93.33%, and using mechanics 20%. It means that the students need to learn more about hortatory exposition text.